A new Rogue-like Escherichia phage UDF157lw to control Escherichia coli O157:H7 - Liao, Yen-Te; Ho, Kan-Ju; Zhang, Yujie; Salvador, Alexandra; Wu, Vivian C. H. (Frontiers in Microbiology, 2024)
Shiga toxin-producing E. coli O157:H7 is one of the notorious foodborne pathogens causing high mortality via consumption of contaminated food. The food safety risk from STEC pathogens could escalate when a group of bacterial cells aggregates to form a biofilm. Bacterial biofilm can diminish the effects of various antimicrobial interventions and enhance the pathogenicity of the pathogens. Therefore, it is an urgent need to have control measurements. Bacteriophages can kill the target bacterial cells through lytic infection, and some enzymes produced during the infection pose the capability to penetrate the biofilm for mitigation compared to traditional interventions. This study aimed to characterize a new Escherichia phage vB_EcoS-UDF157lw (or UDF157lw) and determine its antimicrobial efficacy against E. coli O157:H7. Phage characterization included biological approaches, including phage morphology, one-step growth curve, and stability test (pH and temperature), and genomic approaches (whole-genome sequencing). Later, antimicrobial activity tests were conducted, including productive infection against the susceptible bacterial strains, in vitro antimicrobial activity, and anti-biofilm tests. UDF157lw is a new member of the Rogunavirus phages, containing a long and non-contractile tail, isolated from bovine feces and shares close genomic evolutionary with Escherichia phages vB_EcoS-BECP10 and bV_EcoS_AKS96. Phage UDF157lw had a latent period of 14 min and a burst size of 110 PFU per infected cell against E. coli O157:H7 (ATCC35150). The phage remained viable in a wide range of pH (pH4 to pH11) and temperature (4 to 60 °C). No virulence genes, such as stx, lysogenic genes, and antibiotic resistance genes, were found. Phage UDF157lw demonstrated high infection efficiencies against different E. coli O157:H7 and generic E. coli strains. In addition, UDF157lw encoded a unique major tail protein (ORF_26) with prominent depolymerase enzyme activity against various E. coli O157:H7 strains, causing large plaque sizes. In contrast to the phage without encoding depolymerase gene, UDF157lw was able to reduce 24h and 48-h E. coli O157:H7 biofilm after 1-h phage treatment. The findings of this study provide insight into a new member of the Rogunavirus phages and demonstrate its antimicrobial potential against E. coli O157:H7 in vitro.